Quality of life of women after the mastectomy - Musiał, Zofia; Sendecka, Wioletta; Zalewska-Puchała, Joanna (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Introduction. The breast cancer is the most frequent cancer appearing at women which in numerous cases requires the mastectomy. The mastectomy is a great experience for women and many times is leading qualities of life to the decrease. They at present are aspiring taken medical interventions not only to cure, but also improved the quality of life of patients. Aim. The evaluation of the quality of life of women after the mastectomy. Material and methods. Seventy women consisted in the Club of the Amazons were provided with examinations. They used the questionnaire of the questionnaire form of the own structure and the standardized WHOQOL-BREF questionnaire. The analysis was performed with the STATISTICA 7.1 program. Results. The mastectomy influences women’s general negatively. At most quality of life is being assessed in physical field, and most low in psychological field. The age and the occupational activity have essential statistically influence on quality of life. The reconstructive operation and breast prosthesis improve noticeable quality of life of women after the mastectomy. Conclusions. Quality of life women after mastectomy remained in the study group in the middle range of scale WHOQL-BREF questionnaire. Nursing Topics 2013; 21 (1): 38–46